Light induced DEP for immobilizing and orienting Escherichia coli bacteria. (January 2016) - Miccio, Lisa; Marchesano, Valentina; Mugnano, Martina; Grilli, Simonetta; Ferraro, Pietro
Abstract: Manipulating bacteria and understanding their behavior when interacting with different substrates are of fundamental importance for patterning, detection, and any other topics related to health-care, food-enterprise, etc. Here, we adopt an innovative dielectrophoretic (DEP) approach based on electrode-free DEP for investigating smart but simple strategies for immobilization and orientation of bacteria. Escherichia coli DH5-alpha strain has been selected as subject of the study. The light induced DEP is achieved through ferroelectric iron-doped lithium niobate crystals used as substrates. Due to the photorefractive (PR) property of such material, suitable light patterns allow writing spatial-charges-distribution inside its volume and the resultant electric fields are able to immobilize E. coli on the surface. The experiments showed that, after laser irradiation, about 80% of bacteria is blocked and oriented along a particular direction on the crystals within an area of few square centimeters. The investigation presented here could open the way for detection or patterning applications based on a new driving mechanism. Future perspectives also include the possibility to actively switch by light the DEP forces, through the writing/erasing characteristic of PR fields, to dynamically control biofilm spatial structure and arrangement. Highlights: Light induced DEP allows to immobilize E. coli . Lithium Niobate is funcionalized to trap bacteria cell on its surface. Manipulation of bacteria at large scale is demonstrated.